2023
DOI: 10.1038/s41421-022-00485-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of a dual genetic system to decipher exocrine cell fate conversions in the adult pancreas

Abstract: Unraveling cell fate plasticity during tissue homeostasis and repair can reveal actionable insights for stem cell biology and regenerative medicine. In the pancreas, it remains controversial whether lineage transdifferentiation among the exocrine cells occur under pathophysiological conditions. Here, to address this question, we used a dual recombinase-mediated genetic system that enables simultaneous tracing of pancreatic acinar and ductal cells using two distinct genetic reporters, avoiding the “ectopic” lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In the emergence of acute pancreatitis, there is a pivotal cellular event in which the pancreatic acinar cells differentiate to CK19 + ductal-like cells, a cellular process known as acinar-to-ductal metaplasia (ADM)(2, 24, 25). Given that ADM is a hallmark feature of acute pancreatitis, we examined the spatial distribution of CK19 + cells to identify potential cell types that might interact with them.…”
Section: Resultsmentioning
confidence: 99%
“…In the emergence of acute pancreatitis, there is a pivotal cellular event in which the pancreatic acinar cells differentiate to CK19 + ductal-like cells, a cellular process known as acinar-to-ductal metaplasia (ADM)(2, 24, 25). Given that ADM is a hallmark feature of acute pancreatitis, we examined the spatial distribution of CK19 + cells to identify potential cell types that might interact with them.…”
Section: Resultsmentioning
confidence: 99%
“…In the research of cell fate conversion among exocrine cells, previous studies have been contradictory about the contribution of ductal cells to acinar cells in adults, 28–30 as is the case with acinar‐to‐ductal metaplasia 31,32 . Based on a sequential recombination system, Tnni3‐Dre;CK19‐CreER;IR1 mice were generated to label ductal cells and acinar cells with different fluorescent proteins 33 . Given that CK19 is expressed in the majority of ductal cells and few acinar cells, constitutive Dre‐mediated Dre‐ rox recombination preferentially and specifically occurs in Tnni3 + acinar cells, preventing the ‘ectopic’ labelling by CK19‐CreER in acinar cells.…”
Section: Dual‐recombinase‐mediated Lineage Tracing Via Or‐logicmentioning
confidence: 99%
“…31,32 Based on a sequential recombination system, Tnni3-Dre; CK19-CreER;IR1 mice were generated to label ductal cells and acinar cells with different fluorescent proteins. 33 Given that CK19 is expressed in the majority of ductal cells and few acinar cells, constitutive Dre-mediated Dre-rox recombination preferentially and specifically occurs in Tnni3 + acinar cells, preventing the 'ectopic' labelling by CK19-CreER in acinar cells. In this way, the two types of cells can be labelled with distinct genetic markers simultaneously (Figure 1E, F).…”
Section: Lineage Transdifferentiation Between Acinar Cells and Ductal...mentioning
confidence: 99%
“…The vast majority of the pancreas is exocrine pancreas, and about 95% of the exocrine pancreas consists of acinar cells and duct cells [ 2 , 3 ]. The pancreatic acinar cells produce and release many digestive enzymes, including amylases, lipases, and proteinases, while the ductal cells transport these enzymes into the duodenum [ 4 ]. Li et al also found that adult pancreatic acinar cells might be an important source of β-cell neogenesis [ 5 ].…”
Section: Introductionmentioning
confidence: 99%